Audit Quality and Idiosyncratic Stock Price Volatility: Evidence from Auditor Tenure and Big Four Auditors in Indonesian Non-Financial Firms - Andhita Rosy Febrina; Ika Atma Kurniawanti (Politeknik Ganesha Medan, 2026)
This study examines the relationship between auditor tenure, audit firm size, and idiosyncratic stock price volatility. Idiosyncratic volatility reflects firm-specific risk arising from uncertainty related to a company’s future performance. Using a sample of non-financial firms listed on the Indonesia Stock Exchange during the period 2013–2017, this study employs annual financial statements, audit reports, and weekly stock price data. Idiosyncratic stock price volatility is measured using the Stock Price Idiosyncratic Volatility (SPIV) approach derived from the market model. Multiple linier regression is applied to test the hypotheses. The results show that auditor tenure has a significant negative effect on idiosyncratic stock price volatility, indicating that longer auditor–client relationships improve auditors’ understanding of client operations and enhance financial reporting credibility. Furthermore, firms audited by Big Four audit firms exhibit lower idiosyncratic stock price volatility, suggesting that higher audit quality reduces information asymmetry and firm-specific risk perceived by investors. Several control variables, including trading volume, firm size, market-to-book ratio, and business segments, are also found to significantly influence idiosyncratic volatility. These findings highlight the role of audit quality as an important governance mechanism that improves information transparency and contributes to more stable stock prices in the Indonesian capital market.